Answer:
Given:
Given expression:
[tex]\dfrac{30pqr(p+q+r)}{(p+q)(p+r)}[/tex]
Substitute given values into given expression:
[tex]\implies \dfrac{30\cdot\dfrac12\cdot-\dfrac13\cdot\dfrac15\left(\dfrac12-\dfrac13+\dfrac15\right)}{\left(\dfrac12-\dfrac13\right)\left(\dfrac12+\dfrac15\right)}[/tex]
[tex]\implies \dfrac{-\dfrac{30}{30}\left(\dfrac{15}{30}-\dfrac{10}{30}+\dfrac{6}{30}\right)}{\left(\dfrac36-\dfrac26\right)\left(\dfrac{5}{10}+\dfrac{2}{10}\right)}[/tex]
[tex]\implies \dfrac{-1\left(\dfrac{11}{30}\right)}{\left(\dfrac16\right)\left(\dfrac{7}{10}\right)}[/tex]
[tex]\implies \dfrac{-\dfrac{11}{30}}{\dfrac{7}{60}}[/tex]
[tex]\implies -\dfrac{11}{30}\times \dfrac{60}{7}[/tex]
[tex]\implies -\dfrac{660}{210}[/tex]
[tex]\implies -\dfrac{22}{7}[/tex]